2023
DOI: 10.4314/ahs.v23i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between fear of COVID-19 and pregnancy distress

Abstract: Background: Mental health problems experienced during pregnancy negatively affect both maternal and fetal wellbeing. Objective: This study aimed to investigate the relationship between fear of COVID-19 and pregnancy distress in healthy pregnant women living in Turkey. Methods: A descriptive, relational/cross-sectional study was conducted by interviewing 363 pregnant women in person. Data were collected using a personal information form, the Fear of COVID-19 Scale (FCV-19S), and the Tilburg Pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Some authors have reported moderate levels of fear of the disease in pregnant women one year after the start of the pandemic. 17 Fear during pregnancy may represent a relevant risk factor in the normal development of the current pregnancy; some authors point out an incidence between 45% and 77%. 2,49,50 In this regard, there is research on the consequences that fear can have on infant psychophysiological development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported moderate levels of fear of the disease in pregnant women one year after the start of the pandemic. 17 Fear during pregnancy may represent a relevant risk factor in the normal development of the current pregnancy; some authors point out an incidence between 45% and 77%. 2,49,50 In this regard, there is research on the consequences that fear can have on infant psychophysiological development.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 However, there are few studies related to vulnerable population groups such as pregnant women. 16,17 In addition, psychological reactions secondary to health crises seem to persist over time 18 and in this sense, the presence of fear and anxiety on an ongoing basis and in the prenatal period constitutes one of the precursors of postpartum depression. [19][20][21] Although the measures taken over the last three years have been fundamental in minimising the effects of the disease, this may have had a high psychological cost for certain population groups that needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%